2020
DOI: 10.1101/2020.07.19.211318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A disynaptic circuit in the globus pallidus controls locomotion inhibition

Abstract: Basal ganglia (BG) inhibit movement through two independent pathways, the indirect- and the hyperdirect-pathways. The globus pallidus (GP) has always been viewed as a simple relay within these two pathways, but its importance has changed drastically with the discovery of two functionally-distinct cell types, namely the prototypic and the arkypallidal neurons. Classic BG models suggest that all GP neurons receive GABAergic inputs from striato-pallidal indirect spiny projection neurons and glutamatergic inputs f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 75 publications
(129 reference statements)
8
28
0
Order By: Relevance
“…Only a subset of recorded PV + neurons (8 out of 18, 44.4%) showed detectable Foxp2 + input, and the strength of this connection was the weakest among all connection types examined (Foxp2 + to PV + vs. PV + to PV − , P = 0.00023; Foxp2 + to PV + vs. Npas1 + to Npas1 − , P = 0.0053; Foxp2 + to PV + vs. Npas1 + to PV + , P = 0.0047) ( Table 6 ). The observation of this weak and likely biologically negligible connection is highly consistent with recent studies (Aristieta et al, 2020; Ketzef and Silberberg, 2020). As it was clear that the Npas1 + input targets PV + neurons, these results collectively imply that PV + neurons receive Npas1 + input largely from the Nkx2.1 + (aka Npr3 + ) subpopulation, which do not express Foxp2 ( Figure 1c ), see also (Abecassis et al, 2020).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Only a subset of recorded PV + neurons (8 out of 18, 44.4%) showed detectable Foxp2 + input, and the strength of this connection was the weakest among all connection types examined (Foxp2 + to PV + vs. PV + to PV − , P = 0.00023; Foxp2 + to PV + vs. Npas1 + to Npas1 − , P = 0.0053; Foxp2 + to PV + vs. Npas1 + to PV + , P = 0.0047) ( Table 6 ). The observation of this weak and likely biologically negligible connection is highly consistent with recent studies (Aristieta et al, 2020; Ketzef and Silberberg, 2020). As it was clear that the Npas1 + input targets PV + neurons, these results collectively imply that PV + neurons receive Npas1 + input largely from the Nkx2.1 + (aka Npr3 + ) subpopulation, which do not express Foxp2 ( Figure 1c ), see also (Abecassis et al, 2020).…”
Section: Resultssupporting
confidence: 92%
“…The cellular mechanisms that mediate motor-suppression have yet to be identified. While Foxp2 + neurons have been proposed to send “stop” signals to the striatum (Mallet et al, 2016; Aristieta et al, 2020; Goenner et al, 2020), it is likely that multiple circuit elements are involved in producing complete behavioral arrest (Schmidt et al, 2013; Jahanshahi et al, 2015; Wessel and Aron, 2017). On the other hand, it is clear that the inhibitory projection to the STN (and substantial pars reticulata) mediates the motor-promoting effects, and it is consistent with the established relationship between STN activity and movement suppression (Hamani et al, 2004; Aron and Poldrack, 2006; Aron et al, 2007; Eagle et al, 2008; Schmidt et al, 2013; Schweizer et al, 2014; Fife et al, 2017; Wessel and Aron, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be a result of the cautious approach to minimize the expression of the ChR2 virus outside of the GPe. However, ex vivo validation of our in vivo observations supports low local arkypallidal-mediated inhibition, as suggested recently (Aristieta et al, 2020). The afferent pathways to the GPe have been described previously (Albin et al, 1989;Cazorla et al, 2014;DeLong, 1990;Kawaguchi et al, 1990;Kita et al, 1983;Robledo and Fé ger, 1990;Wu et al, 2000); however, their effect on the different GPe subpopulations was unknown.…”
Section: Ll Open Accesssupporting
confidence: 88%
“…Our finding that iSPN-PV + input is stronger than iSPN-Npas1 + input is consistent with earlier anatomical studies showing that iSPNs form more synaptic contacts with PV + neurons compared to PV − neurons (Yuan et al, 2017). In addition, it is in line with recent electrophysiological studies that iSPNs strongly target Nkx2.1 + neurons (which are dominated by PV + neurons) while providing minimal input to Foxp2 + neurons (which are a subset of Npas1 + neurons) (Yuan et al, 2017; Aristieta et al, 2020; Ketzef and Silberberg, 2020). Furthermore, we showed that the selective targeting of iSPN input to PV + neurons was topographically conserved between spatial subdomains within the dStr—the DMS and the DLS.…”
Section: Discussionsupporting
confidence: 87%